Behind the Cancellation of Green Refinery Cooperation Between Pertamina and Eni: An Analysis of Domestic and Regional Aspects - Rachman, Muhammad Fauzi Abdul; Yani, Yanyan Mochamad; Montratama, Ian (Department of International Relations Universitas Pertamina, 2021)
Pertamina and Eni faced double strike problems. The Italian government did not grant the license for building Indonesian crude palm oil (CPO) based green finery to Eni-Pertamina as most Indonesian CPO producers do not possess RSPO certificates and the EU restricts the use of CPO. The policies resulted in opportunities loss for Pertamina and Eni in 2019. This qualitative paper examined the logical reasons behind the Italian government decision by two levels of analysis, domestic and regional locus. The finding shows that domestically, political circumstances among parties and figures, other than CPO commodities farmers, played a significant role in the cancellation. The historical instability in Italy domestic political situation also brought it closer to revocation. On another level, the ups and downs of Italy-the EU relations before and during Conte I and Conte II government were a regional reason behind it.